(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Trauma is a leading cause of death in children older than one year in the world; with head trauma representing 80% or more of the injuries. Most head injuries in children occurs secondary to motor vehicle accidents, falls, assaults, recreational activities, and child abuse. Objectives:To evaluate head trauma in pediatrics age group regarding age, sex, presenting symptoms and signs and the line of management; to know the role of CT scan in assessment of pediatrics head trauma, and t determine the extent of pediatric head trauma in Baghdad city. Methods: Fifty neurosurgical pediatrics cases with head trauma between the age of one year to fourteen years whom presented to the neurosurgical ward in Al-Imamain Al-kadhimain Medical City. Questioner for gender, age, mechanism of injury, presented signs and symptoms, consciousness, CT scan findings, and the line of management. Results:The study showed that males have the higher incidence with 72%. Head injury due to road traffic accident accounting for 44%. The loss of consciousness was documented in 60% of the cases. All patients subjected to CT scan imaging modality for assessing head injury as the ideal way. The presence of hematoma was seen in 68% of the cases. Associated injuries were seen in 60% of cases. Vomiting as an important symptom in pediatrics head trauma encountered in 52% of the patients. The developments of fits are very important sequel encountered in 16%. The close monitoring and follow up being the most common line of management accounting for 88%. Conclusion:Pediatrics head trauma is a common problem with males have higher incidence than females. The most common mechanism of injury was road traffic accident. CT scan is a very vital and important diagnostic tool in evaluating patient with head trauma. Key words:Pediatrics, head trauma.